Optimization of Banyuwangi Festival Management through ERP-Tourism Using Dashboard - Pramuditya Soesanto , Rayinda; Ibnu Zulkarnain; Adya Pramudita, Aloysius; Andrawina, Luciana (Metris: Jurnal Sains dan Teknologi, 2024)
Tourism is an economic sector that has an important role in regional economic growth, including in Banyuwangi Regency. Banyuwangi Festival, as one of the main attractions, faces various challenges in its management, ranging from event coordination to performance monitoring. This research aims to optimize the management of Banyuwangi Festival through the implementation of Enterprise Resource Planning (ERP)-Tourism supported by the use of interactive dashboards. This research utilizes the Rapid Application Development (RAD) method, which involves various stakeholders in the system development process. The research findings show that the implementation of ERP-Tourism and interactive dashboards is able to improve the efficiency, effectiveness, and quality of festival management. The theoretical implications of this research include the development of literature related to the use of ERP technology in the tourism sector and its contribution to event management. Practically, the results of this study can be used as a guide for festival managers in improving the quality and efficiency of their events. Recommendations for future research include expanding the application of the ERP-Tourism system to other tourism events in Banyuwangi and other regions, as well as further developing dashboard features to meet the specific needs of different types of events. Thus, it is expected that this system can provide wider and sustainable benefits to the tourism sector and regional economy